KUALITAS DAGING DOMBA YANG DIBERI PAKAN SILASE LIMBAH SAYURAN - Falahudin, Aaf; Imanudin, O. (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
The objective of this research is to get information the quality of lamb meat fed with vegetables waste silage. The experiments was conducted using 24 local male sheep 8 - 10 months old with weight between 15 - 20 kg. The experimental design used was Completely Randomized Design with 6 treatments and 4 replications. The treatments applied were as follows: T0 = 100% green grass + 0% vegetable waste silage + T1 = 80% green grass + 20% vegetable waste silage, T2 = 60% forage grass + 40% vegetable waste silage, T3 = 40% forage grass + 60% vegetable waste silage, T4 = 20% forage grass + 80% vegetable waste silage and T5 = 0% forage grass + 100% vegetable waste silage. The experiment was carried out for 6 weeks with a 2-week adaptation period. The results showed that vegetable waste silage significantly different results on dry matter consumption, daily weight gain and meat protein, but did not provide significant results for the physical quality of male local lamb meat such as color, weight loss and pH. The best treatment is forage feed 60% and vegetable waste silage 40% with dry matter consumption of 720.38 g/day, daily body weight 88.18 g/day, meat protein 21.05%, color of meat bright red, weight loss 28.57% and pH 5.70. Keywords: Silage, Vegetable Waste, Dry Matter Consumption, Daily Weight Gain, Quality of Lamb Meat